Macroeconomic Modernization of the National Economy Regarding the Supply Chain Management of the National Economy’s Competitiveness - Safonov, Yurii; Markina, Iryna; Borshch, Viktoriia; Maslennikov, Yevgen; Poberezhets, Olha (ExcelingTech, 2020)
Abstract— The purpose of this study is to investigate the effect of supply chain management on competitive advantage and sustainability in the national economy. The national economy’s competitiveness has a complex nature, ensured by sustainable economic, political and social development. In the paper the issue of the national economy’s competitiveness as a complex of supply chain management of socio-economic system is researched. The author’s approach to the concept of the national economy’s competitiveness was formed. Key elements of the national economy’s competitiveness were analyzed, among which national production, resource base, intelligence of the Nation, and national social capital. Relationships between the competitiveness of the national economy and globalization processes are determined. Practical recommendations for improving competitiveness of the developing countries in the world economic area were proposed. Problem of the national economy’s competitiveness is examined from the position of the modern macroeconomic modernization, under supply chain system and institutional dynamics are one of the key factors for promoting economic progress and ensuring society’s high level of well-fare.